Internal labour market as factor in the career success perceived by an engineer - Bejarano Heredia, Alberto Ismael (2011)
The phenomenon of the global crisis in both the financial energy sectors as well as the emergence of new technologies companies consider their success or failure depending on the ability to respond quickly to opportunities in their competitive environment. This competitiveness is found especially in the capacity of their technical professionals. On the other hand career is characterized as protean, boundaryless and directed mainly by the individual. Given this scenario, organizations should organize an internal labor market to attract, develop and retain talent. The purpose of this research is to study the impact of internal labour market and subjective career success perceived by engineers in organizations. For the study a survey was conducted via email to 1135 graduates with a response rate of 89.07%. Structural equations were then applied to identify relationships. The results show a positive relationship between internal labour market and subjective career success perceived by engineers working in the organization. The conclusions of the study can help engineers and companies to drive the careers of these knowledge workers as a way to help them to be happier and help their companies to have more dynamic and proactive engineers. At the same time, educational institutions with engineering programs will gain a better understanding of an engineer’s career, and will be able to use this knowledge to review the effectiveness of their educational programs.